The Development of Sport Culture Indicators for Sports Avenue - Zhao, Jingwen; Mahakhan, Phattaraphon; Hongsaenyatham, Prakit (International Journal of Sociologies and Anthropologies Science Reviews, 2024)
Background and Aim: China has officially entered a new era of reform, marking that the construction of university sports culture has also ushered in a new era and new challenges. Therefore, this research aims to develop the sports culture indicators for sports avenues. Materials and Methods: The expert group members of this study are mainly university physical education teachers in Xi’an, leaders of Xi' a Sports Bureau, and grass-roots front-line teachers. All the selected experts have a rich theoretical basis and practical experience in constructing campus sports culture. Five people were selected by IOC, 25 people were selected by Cronbach reliability test, 19 experts by Delphi method, and 122 people for empirical research. Hierarchical Analysis YAAHP6.0 software is used to calculate the weight and consistency of each index and data processing of Fuzzy Comprehensive Evaluation Method Matlab software is used to analyze the data. Results: The evaluation index system of university sports culture construction in Xi'an is constructed. The first-level indicators include sports spirit and culture, sports material culture, sports system culture, and sports behavior culture. The secondary index includes 9 aspects. There are 24 three-level indicators, covering all key aspects of the construction of campus sports culture. Conclusion: The evaluation index system proposed in this study is comprehensive, systematic, and scientific, which can provide effective tools for the evaluation and decision-making of the sports culture construction in Xi'an universities. The evaluation index system is scientific, systematic, and practical.